Diagnóstico do processo de torneamento do aço inoxidável ABNT 304 a partir do estudo da formação do cavaco - Silva, Flávia Cristina Sousa e (2007)
Stainless steels are materials that generally present low machinability mainly because the high ability to workharden during the cutting process and the long chips produced that lead to a rapid tool wear. It is possible that there is a correlation between tool wear and chip morphology, and therefore, the chip formed could give a diagnosis of the process. In this work turning experiments were carried out in ABNT 304 stainless steel using coated cemented carbides tools. During the operation, tool wear was monitored and chips samples collected for different tool wear stages to be analyzed. Chip thickness was measured for each sample and chip thickness ratio and primary shear plane angle were calculated. Some metallographic analysis of the samples was also used to identify some characteristics of the process. The chips were also classified into different types and shapes. During the operation, chip temperature was measured using infrared sensor. Some samples from quick-stop experiments were analyzed to get information about flow zone thickness. The results showed that it is possible to establish a relation between tool wear and chip morphology. There is also a good correlation between tool wear and chip temperature. The results show that temperature increases with tool wear.